Comparative Analysis of Selected Heavy Metal Concentrations in Cucumbers Cultivated Inside and Outside Greenhouses in Randomly Selected Farms West of Tripoli - Zahrah S. Ghoulah; Howida A. Almadne; Farag S. Awen; Souad Mohamed Kshed (African Journal of Advanced Pure and Applied Sciences, 2025)
This study aimed to determine the concentrations of selected heavy metals (lead, cadmium, and chromium) in cucumber samples produced in greenhouses and open-field farms west of Tripoli, Libya. Using Flame Atomic Absorption Spectroscopy (FAAS) The results for naturally grown (open-filed) cucumbers were compared with those from greenhouse cultivation. Furthermore, the concentrations were compared against the maximum permissible limits set by Libyan and international standards, expressed in mg/kg of fresh weight. The study also investigated the relationship between the cultivation method, geographical variations, and their impact on the concentrations of these elements in the cucumber samples. A total of 20 cucumber samples were randomly collected from several farms extending from Janzur to Sabratha (12 from greenhouses and 8 from open fields). The samples were stored in plastic bags and subsequently digested using concentrated nitric acid (65%).The elemental concentrations were measured using FAAS. The results revealed high concentrations of lead (Pb), with an average of 0.440 mg/kg in open-field cucumbers and 0.641 mg/kg in greenhouse cucumbers (fresh weight). These levels exceed the maximum permissible limit of 0.1 mg/kg established by both Libyan and international standards. For chromium (Cr), the average concentration was 0.130 mg/kg in open-field cucumbers and 0.192 mg/kg in greenhouse cucumbers. These concentrations are below the international maximum allowable limit (0.5 mg/kg), noting that no specific Libyan standard exists for chromium in vegetables. Regarding cadmium (Cd), its concentrations in all samples were below the instrument’s limit of detection (<0.01 mg/L).